PEMUTIHAN TERUMBU KARANG - Santoso, Arif Dwi (Jurnal Hidrosfir Indonesia, 2006)
Corral reef in Indonesia is one of the ecosystem would be heavily damagedas same as a rain forest ecosystem. The main source of damage come fromhuman activities as land base pollution activity and un-wise fishing.Meanwhile, above problem didn’t solve clearly, The potencial threat hasbeen occured. Corral reef has bleach since climate change occur in the fewdecades. This article showed about what is corral reef bleacing, what is themain problem and how to conserve it.